Measuring the influence of FinTech innovation towards consumers’ attitude: Moderating role of perceived usefulness - Al Mamun, Mohammad Abdullah; Tanchangya, Tipon; Rahman, Md Abidur; Hasan, Md Mehedi; Islam, Naimul; Yeamin, Bony (Elsevier, 2025)
The study aims to investigate the contribution of perceived usefulness (PU) in shaping consumer attitudes towards FinTech innovations in Bangladesh. Additionally, this investigation seeks to examine the direct effect of FinTech innovation, including performance expectancy (PE), effort expectancy (EE), social influence (SI), facilitating conditions (FC), perceived financial risk (PFR), and perceived security risk (PSR) on FinTech service users’ attitudes (ATT). This inquiry integrated Technology Acceptance Model (TAM), the Unified Theory of Technology Acceptance and Use (UTAUT), and Perceived Risk Theory (PRT) to develop a theoretical framework. A convenience sampling approach is employed for data collection, and 398 respondents’ information is included. However, this research reveals that PE, EE, SI, and FC have affected ATT positively and significantly, while PFR and PSR have weaker but statistically significant impacts on ATT. This study provides insights, both theoretical and practical, for future researchers and policymakers.